A first report of decapod crustaceans (Anomura and Brachyura) from Laje de Santos: a no-take marine reserve in the southeast coast of Brazil - Moraes, Isabela R. R. [UNESP]; Davanso, Thiago M. [UNESP]; Da Silva, Alexandre R. [UNESP]; Cobo, Valter J.; Alves, Douglas F. R.; Santana, William [UNESP]; Mantelatto, Fernando L.; Castilho, Antonio L. [UNESP] (Inst Biologia, Univ Nacional Autonoma Mexico, 2022)
This study represents an unprecedented effort to assess the diversity of rocky infralittoral decapods Brachyura and Anomura from the Marine State Park of Laje de Santos, a preserved and protected area located in the southeastern Brazilian coast. Sampling was carried out quarterly for 1 year, using the combination of artificial refuge substrate (ARS) for the passive capture of specimens, and SCUBA diving for active capture. A total of 987 individuals distributed into 32 species, 22 genera, and 11 families were determined. We present a taxonomic account of the species and their distribution records are discussed. The hermit crab Pagurus brevidactylus and the crab Mithraculus forceps were the most common species of Anomura and Brachyura, respectively. As expected, the combination of the sampling methodologies showed a higher Shannon diversity index value (H = 5.7), than the individual methods of ARS (H = 5.6) and active capture (H = 4.4). This study provides the first record of decapod crustaceans for the park, therefore it can be used as a baseline for local fauna monitoring programs and conservation planning.
Keywords: Ecology; Fauna; Marine invertebrates; Protected area